PEMBERDAYAAN MASYARAKAT DALAM OPTIMALISASI PENURUNAN STUNTING: STUDI KASUS DESA COT KEUMUDEE PEUSANGAN - Cut Azizah; Putra Arief Fonna; Muhammad Faza; Mohd Hibban Machruza; Yuza Fariana; Nuraina Nuraina (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2022)
Cases of short toddlers constitute the highest prevalence compared to other nutritional problems such as undernutrition, underweight and obesity. The prevalence of short toddlers increased from 2016 by 27.5% to 29.6% in 2017. The prevalence of short toddlers in Indonesia tends to be static. The results of Basic Health Research (Riskesdas) in 2007 showed the prevalence of short toddlers in Indonesia at 36.8%. In 2010, there was a slight decline to 35.6%. But the prevalence of short toddlers again increased in 2013 to 37.2%. The prevalence of short toddlers resulted in Riskesdas in 2018 to 27.7%. As an effort by the government to accelerate the decline in stunting in Indonesia, the President of the Republic of Indonesia issued Presidential Regulation of the Republic of Indonesia Number 72 of 2021 on accelerating the decline of stunting. The regulation strengthens stranas and institutional intervention frameworks in accelerating the decline of stunting. The purpose of its implementation is: 1) increase public knowledge about the fulfillment of nutrition in toddlers especially stunting toddlers; 2) provide understanding to the public to utilize moringa leaves and cooking oil in nutritional fulfillment in toddlers and especially those who experience stunting; 3) Empowering people to plant moringa trees so that they can be used in the fulfillment of daily life nutrition.  Activities carried out to achieve the purpose of service activity are to provide socialization, education, monitoring, moringa trees planting counseling and discussion, as well as community joint evaluation to provide knowledge to the community  about stunting and PHBS.